Timing and severity of crop load management influences technological maturity, terpene synthase expression and free terpene accumulation in Gewürztraminer grapes (Vitis vinifera L.). (2nd August 2022) - Kovalenko, Y.; VanderWeide, J.; Tindjau, R.; Zandberg, W.F.; Castellarin, S.D.
Abstract: Background and Aims: Terpenes are volatile organic compounds that influence the composition of many winegrape cultivars. Terpene accumulation is variable between seasons and locations, influencing vintage composition. Crop load management (CLM) is a cultural practice utilised to improve grape composition; however, the impact of CLM on terpene biosynthesis and accumulation in winegrapes remains largely unknown. Methods and Results: Crop load management was applied to Gewürztraminer vines at two developmental stages: bunch closure [early (E)] and veraison [late (L)], and two crop loads: 50% removal [light crop (LC)] and 25% removal [medium crop (MC)] and compared to a Control [high crop (HC)] over three seasons. We considered early‐harvest (22.5°Brix in HC) and harvest (23.4°Brix in HC) dates. The LC treatments improved TSS at both harvests; however, LC‐E accelerated ripening compared to LC‐L. The concentration of total free terpenes was highest in LC‐E only at early‐harvest. Free α‐phellandrene, β‐citronellol, geranic acid, geraniol, myrcene and nerol dictated this pattern. Although LC‐E increased glycosylated geraniol at early‐harvest, the concentration of total glycosylated terpenes was not altered. The expression of four terpene synthase (TPS) genes was increased by LC‐E at early‐harvest. Conclusions: The LC‐E treatment accelerated technological maturity, and increased the expression of TPSs and free terpene accumulation at the early‐harvest stage. Significance of the Study: This work provides valuable insight into the capacity of CLM to modulate terpenes in aromatic winegrapes.